Drying of pomegranate seeds using infrared radiation - Doymaz, Ibrahim (KOREAN SOCIETY FOOD SCIENCE & TECHNOLOGY-KOSFOST, 2012)
Effect of different infrared (IR) power levels on drying kinetics of pomegranate seeds was investigated. The pomegranate seeds were dried at 83, 104, 125, and 146 W IR power levels. It was observed that the power levels affected the drying rate and time. Drying time reduced from 150 to 60 min as the IR power level increased from 83 to 146 W. The experimental data obtained from drying study were fitted with 10 mathematical models to evaluate the drying kinetics of the pomegranate seeds. The Page, Midilli et al., and Weibull models are given better prediction than the other models and satisfactorily described drying kinetics of pomegranate seeds. Effective diffusivity varied from 1.96 to 6.29x10(-11) m(2)/s and was significantly influenced by IR power.
Keywords: activation energy; effective diffusivity; infrared (IR) drying; mathematical modelling; pomegranate seed; EFFECTIVE MOISTURE DIFFUSIVITY; BY-PRODUCTS; KINETICS; SLICES; LEAVES; GRAPE; Food Science & Technology